2012
DOI: 10.1159/000345494
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Factors Influence the Prognosis of Diabetic Macular Edema after Pars Plana Vitrectomy with Internal Limiting Membrane Peeling

Abstract: Background: To evaluate the prognostic factors for the best-corrected visual acuity (BCVA) and foveal average retinal thickness after vitrectomy with internal limiting membrane (ILM) peeling for diabetic macular edema. Design: Retrospective, single-center study. Participants: This study involved 31 eyes of 27 patients who had undergone vitrectomy with ILM peeling between January 2005 and March 2008. Methods: Relationships between preoperative systemic or ocular factors and BCVA or foveal average retinal thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In particular, the HbA1c level can affect the resolution of edema after PPV with or without ILM peeling. 15,43,51,54 Thus, it is difficult to exclude effects of these systemic factors on visual outcome in comparative studies without a study design on bilateral DME. However, no previous studies used bilateral DME to compare between PPV with ILM peeling and PPV alone.…”
mentioning
confidence: 99%
“…In particular, the HbA1c level can affect the resolution of edema after PPV with or without ILM peeling. 15,43,51,54 Thus, it is difficult to exclude effects of these systemic factors on visual outcome in comparative studies without a study design on bilateral DME. However, no previous studies used bilateral DME to compare between PPV with ILM peeling and PPV alone.…”
mentioning
confidence: 99%
“…Several studies demonstrate the prognostic factors in eyes with DME when treated by vitrectomy [15,[20][21][22][23]. Various factors including systemic factors [15,23], baseline visual acuity [15,20,21], evidence of PDR [23], prior laser treatment [15], removal of the internal limiting membrane [20], vitreoretinal abnormalities [15,20,22] and retinal thickening [20,21] are reported to be associated with postoperative visual acuity and/or retinal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, we were not able to find these factors as predictors of responsiveness to vitrectomy. The small number of cases [21][22][23], retrospective nature of the study [15,21,23], presence of vitreoretinal abnormalities and assessment of DME without OCT [15,20,22] may have affected the results of their analyses. The main difference of our cohort from those in the previous studies was that the majority of our cases (N = 60, 77.9 %) had been treated by an anti-VEGF agent, which is currently accepted as the mainstay of treatment for DME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that postoperative BCVA was significantly lower in patients without any diabetic treatment before the diagnosis of diabetic retinopathy. 66 These studies suggest that there are retinal, ocular, and systemic factors that can help identify patients who could benefit from surgical intervention for DME. ' …”
Section: Prognostic Factorsmentioning
confidence: 99%